The Effect of Ethanol Extract of Cat's Whiskers Leaves (Orthosiphon stamineus) on Reducing Cholesterol Levels in Female Sprague Dawley Rats - Ira Manda Sari Berampu; Edy Fachrial; I Nyoman Ehrich Lister (Jurnal Penelitian Pendidikan IPA, 2024)
This study aims to test the administration of ethanol extract of cat's whisker leaves (Orthosiphon stamineus) to reduce cholesterol levels in female Sprague Dawley rats. This type of research is a quasi-experiment design using a one group pre-test and post-test design. The population in this study was 30 female Sprague Dawley rats aged ± 3 months with a body weight of around 150-250 grams. Data were analyzed using the t test statistic at = 5%. The results of the research showed that the highest decrease in cholesterol levels was in female Sprague Dawley rats at a test dose of 1000 mg/kgBW and there was an effect of ethanol extract of cat's whisker leaves (Orthosiphon stamineus) on reducing cholesterol levels in female Sprague Dawley rats